Glesatinib, a c-MET/SMO Dual Inhibitor, Antagonizes P-glycoprotein Mediated Multidrug Resistance in Cancer Cells - Cui, Qingbin; Cai, Chao-Yun; Gao, Hai-Ling; Ren, Liang; Ji, Ning; Gupta, Pranav; Yang, Yuqi; Shukla, Suneet; Ambudkar, Suresh V.; Yang, Dong-Hua; Chen, Zhe-Sheng (Frontiers in Oncology, 2019)
Multidrug resistance (MDR) is one of the leading causes of treatment failure in cancer chemotherapy. One major mechanism of MDR is the overexpressing of ABC transporters, whose inhibitors hold promising potential in antagonizing MDR. Glesatinib is a dual inhibitor of c-Met and SMO that is under phase II clinical trial for non-small cells lung cancer. In this work, we report the reversal effects of glesatinib to P-glycoprotein (P-gp) mediated MDR. Glesatinib can sensitize paclitaxel, doxorubicin, colchicine resistance to P-gp overexpressing KB-C2, SW620/Ad300, and P-gp transfected Hek291/ABCB1 cells, while has no effect to their corresponding parental cells and negative control drug cisplatin. Glesatinib suppressed the efflux function of P-gp to [3H]-paclitaxel and it didn’t impact both the expression and cellular localization of P-gp based on Western blot and immunofluorescent analysis. Furthermore, glesatinib can stimulate ATPase in a dose-dependent manner. The docking study indicated that glesatinib interacted with human P-gp through several hydrogen bonds. Taken together, c-Met/SMO inhibitor glesatinib can antagonize P-gp mediated MDR by inhibiting its cell membrane transporting functions, suggesting new application in clinical trials.